Efficient photodiode-type photodetectors with perovskite thin films derived from an MAPbI3 single-crystal precursor. Issue 18 (9th April 2020) - Tao, Hong; Wang, Haoning; Bai, Yuchen; Zhao, Hongyang; Fu, Qiuming; Ma, Zhibin; Long, Hao
Abstract : This research exhibits an efficient photodetector based on a perovskite photosensitive layer derived from an MAPbI3 single-crystal precursor. Abstract : Perovskite photosensitive layers play an important role in the photoelectric properties of photodetectors (PDs). Here, a precursor solution comprising of a methylammonium lead iodide (MAPbI3 ) single-crystal is applied to prepare a perovskite film to enlarge the grain size of the perovskite photosensitive layer and improve the detectivity of the PD device. Compared with the traditional precursor solutions composed of raw-materials (MAI + PbI2 ), the perovskite film derived from the MAPbI3 single-crystal precursor possess high crystalline quality with large grain sizes, enhanced light absorption intensity and long carrier lifetime. Thus, the PD device based on the perovskite photosensitive layer derived from the MAPbI3 single-crystal precursor achieves an improved responsivity of 0.633 A W −1 and an optimized detectivity of 2.502 × 10 11 Jones under 660 nm illumination with a light intensity of 1.25 mW cm −2 at −0.4 V. This research highlights an innovative application of perovskite single-crystals for thin film devices.